SIMULASI PENANGGULANGAN KEBAKARAN DENGAN ALAT SEDERHANA PADA SISWA SISWI MI MUHAMMADIYAH KALIKOTES KLATEN - Ambar Winarti; Romadhani Tri Purnomo; Esri Rusminingsih3,Marwanti; Marwanti; Cori Elsera; Supardi; Ratna Agustiningrum; PuputRisti Kusumaningrum; Fitriana Noor Khayati; Nur Wulan Agustina (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Stikes muhammadiyahKlaten is one of the Muhammadiyah Charities that is engaged in education and health, so it carries the mandate to participate in creating community welfare, especially in the health sector. Efforts that can be made by Stikes Muhammadiyah Klaten in carrying out this mandate are to serve the community. Community service activities are one of the Tri Dharma of Higher Education that must be carried out by all lecturers without exception. This activity can be in the form of counseling, health checks, social services etc. PKM can be carried out independently by the Stikes Muhammadiyah Klaten lecturer, or in collaboration with agencies outside the STIKES. And also students Fire events can occur suddenly, so community empowerment is needed to minimize the factors that cause fires. Efforts to prevent fire are carried out through community service activities by providing simple fire prevention and control training. The purpose of this community service is to provide education to the community, especially students of MI TambongWetanKalikotesKlaten in order to empower the level of human resources when a fire occurs in the area around the residence by using simple tools that are around the residence.